COHORT METHOD: STATISTICAL AND DESIGN FOUNDATIONS – AN ANALYTICAL OVERVIEW - Samadov Firdavs Furqatkhoja ogli, (TADQIQOTLAR, 2025)
Summary: The cohort method represents one of the most significant analytical approaches  in  epidemiological  research,  providing  a  high  degree  of  reliability  in establishing  cause-and-effect  relationships.  This  article  analyzes  the  fundamental design principles of the cohort method, key statistical indicators, and their mechanisms of  application  within  the  research  process.  Differences  between  prospective  and retrospective cohort studies, as well as their respective advantages and limitations, are discussed. Furthermore, methods for calculating statistical indicators such as relative risk (RR) and attributable risk (AR), along with their epidemiological interpretation, are described. The paper also highlights the practical applications of the cohort method, particularly its importance in studying chronic and infectious diseases. The analysis demonstrates that the cohort method serves as a crucial scientific basis for an in-depth examination  of  factors  influencing  disease  development,  assessing  risk  levels,  and developing preventive strategies.